Cytokine Expression of Lung Bacterial Infection in Newly Diagnosed Adult Hematological Malignancies - Li, Zengzheng; Yang, Zefeng; Hu, Peng; Guan, Xin; Zhang, Lihua; Zhang, Jinping; Yang, Tonghua; Zhang, Chaoran; Zhao, Renbin (Frontiers in Immunology, 2021)
Adult patients with hematological malignancies are frequently accompanied by bacterial infections in the lungs when they are first diagnosed. Sputum culture, procalcitonin (PCT), C-reactive protein (CRP), body temperature, and other routinely used assays are not always reliable. Cytokines are frequently abnormally produced in adult hematological malignancies associated with a lung infection, it is uncertain if cytokines can predict lung bacterial infections in individuals with hematological malignancies. Therefore, we reviewed 541 adult patients newly diagnosed with hematological malignancies, of which 254 patients had lung bacterial infections and 287 patients had no other clearly diagnosed infections. To explore the predictive value of cytokines for pulmonary bacterial infection in adult patients with hematological malignancies. Our results show that IL-4, IL-6, IL-8, IL-10, IL-12P70, IL-1β, IL-2, IFN-γ, TNF-α, TNF-β and IL-17A are in the lungs The expression level of bacterially infected individuals was higher than that of patients without any infections (P<0.05). Furthermore, we found that 88.89% (200/225) of patients with IL-6 ≥34.12 pg/ml had a bacterial infection in their lungs. With the level of IL-8 ≥16.35 pg/ml, 71.67% (210/293) of patients were infected. While 66.10% (193/292) of patients had lung bacterial infections with the level of IL-10 ≥5.62 pg/ml. When IL-6, IL-8, and IL-10 were both greater than or equal to their Cutoff-value, 98.52% (133/135) of patients had lung bacterial infection. Significantly better than PCT ≥0.11 ng/ml (63.83% (150/235)), body temperature ≥38.5 ℃ (71.24% (62/87)), CRP ≥9.3 mg/L (53.59% (112/209)) the proportion of lung infection. In general. IL-6, IL-8 and IL-10 are abnormally elevated in patients with lung bacterial infections in adult hematological malignancies. Then, the abnormal increase of IL-6, IL-8 and IL-10 should pay close attention to the possible lung bacterial infection in patients.